1987
DOI: 10.1071/ea9870909
|View full text |Cite
|
Sign up to set email alerts
|

Response of apple trees to soil applications of phosphorus, nitrogen and potassium

Abstract: An experiment was conducted at Manjimup Research Station in Western Australia from 1973 to 1982 to determine the optimum rates of fertilizer applications for apple trees (Granny Smith/MM.104 and Hi Early Red Delicious/MM.104) growing in a P-deficient soil (about 6 mg/g bicarbonate-extractable P). The trees were planted at 6.1 multiply 6.1 m spacings. Superphosphate at 5 or 8 kg/tree consistently increased fruit set, but the increase varied from year to year from 8 to 91%. Weight of prunings increased by 24-29%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Under similar soil conditions Wojcik and Klamkowski (2005) were able to increase the number of flower clusters per tree and consequently yield of a greenhouse-grown 'Jonagold' apple trees as a result of pre-plant P fertilization. Bould and Parfitt (1973), Taylor (1975), Waller (1980), Cripps (1987) and Raese (1998) also found that P fertilization of P-deficient apple trees stimulated development of flower buds.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Under similar soil conditions Wojcik and Klamkowski (2005) were able to increase the number of flower clusters per tree and consequently yield of a greenhouse-grown 'Jonagold' apple trees as a result of pre-plant P fertilization. Bould and Parfitt (1973), Taylor (1975), Waller (1980), Cripps (1987) and Raese (1998) also found that P fertilization of P-deficient apple trees stimulated development of flower buds.…”
Section: Resultsmentioning
confidence: 86%
“…Of total quantity of absorbed P about one-half may be permanently removed from the orchard system either in the form of fruit or by incorporation into unavailable forms within the tree, while the remainder is recycled within the system (Stiles, 1994). There are, in the literature, some reports indicating that P fertilization of apple trees improved vigor (Raese, 1998;Wojcik and Klamkowski, 2005), flowering and yield (Bould et al, 1972;Bould and Parfitt, 1973;Waller, 1980;Cripps, 1987;Raese, 1998), and fruit quality and storability (Martin et al, 1965;Yogaratnam and Sharples, 1982;Webster and Lidster, 1986;Gomez-Cordoves et al, 1996;Raese, 1998;Li et al, 2004;Tomala and Soska, 2004). The vegetative and reproductive responses of apple trees to P fertilization in those experiments were most frequently related to limited P availability in soil and not to low P status.…”
Section: Introductionmentioning
confidence: 91%
“…More recently, several conditions have been identified when apples respond to P fertilization. These include times when apple root length is limited, as when trees are newly planted (Taylor and Goubran, 1975) and when replant disorders further inhibit root growth (Neilsen and Yorston, 1991), or when low soil P levels limit P availability to roots (Cripps, 1987;Raese, 1998). Responses to P application have included increased vigor and accelerated flowering of newly planted trees (Neilsen et al, 1990;Taylor and Goubran, 1975) and increased cropping and increased P concentrations in leaf and fruit tissue of mature trees (Cripps, 1987;Raese, 1998).…”
mentioning
confidence: 99%
“…They found that increasing the rate of applied N from 0 to 200 kg ha À1 increased N concentrations from 7.1 to 7.5 g kg À1 even though yield increased from 0.6 to 1.3 kg plant À1 . For example, Sud and Bhutani [15] reported that increasing the rate of N from 200 to 600 g tree À1 increased leaf N concentration from 21.9 to 27.0 g kg À1 , and Cripps [16] found that N fertilization increased N concentration in Hi Early Red Delicious leaves from 23 to 25 g kg À1 . The magnitude of the increase in plant N concentrations reported in these studies were similar to those shown in Fig.…”
Section: Chemical Composition Of Australian Waxflowers 2325mentioning
confidence: 99%